Analisis Efektivitas Penerapan Konsep 5R dalam Pengelolaan Sisa Makanan di Instalasi Gizi RSJD - Mehdy, Rizal Ady; Yuliamir, Henry (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article analyzes the effectiveness of implementing the 5R concept (Reduce, Reuse, Recycle, Reshare, Resell) in managing food waste at the Nutrition Installation of RSJD Dr. Amino Gondhohutomo. Through a case study approach, this research evaluates the extent to which the 5R concept is applied, identifies factors influencing its effectiveness, and provides recommendations to enhance its practice. The results show that the nutrition installation management staff have successfully implemented the 5R concept, while cleanliness officers are crucial in maintaining environmental hygiene. Positive responses from patients also contribute to food waste management. However, challenges such as awareness and involvement of all parties and limited time and resources still need to be addressed. With collaborative efforts and broader support, the implementation of the 5R concept can become more effective and sustainable in the future, enhancing the quality of food service and food waste management in hospitals.